The Saljuq Dynasty: The History of the Establishment and Development of Civilization - Tumangger, Maruli (Tabayyun : Journal Of Islamic Studies, 2025)
Abstract : The Saljuq Dynasty is one of the dynasties that has ever existed in the history of Islamic government. This dynasty was an independent dynasty independent of the Abbasid Dynasty rule in Baghdad. The Saljuq dynasty made the territory of present-day Afghanistan the center of government, far from Abbasid rule in Baghdad. There are many advances in civilization that were built during the establishment of the Saljuk dynasty, including the establishment of Madrasah Nizamiyah which was once led by a great scholar who was very famous among Muslims, namely Imam Al-Ghazali. This article was written in order to explain the history of the founding of the Saljuq dynasty, the development of its government and the progress of civilization achieved during its reign.